Tracing Fiscal Sustainability in Malaysia - Lau, Evan Poh Hock; Lee, Alvina Syn-Yee (Korea Distribution Science Association, 2021)
One of the concerns in the economic policy circle is the fiscal sustainability. This current research revisit the notion of fiscal sustainability for Malaysia using the Indicator of Fiscal Sustainability (IFS) developed by Croce and Juan-Ramón (2003) where we employ samples of time-series data from 1970 to 2017. The findings reveal that 40 out of 48 years, during which the calculated IFS algorithm is above the threshold of 1, imply Malaysia was fiscally unsustainable. Despite having been fiscally unsustainable, Malaysia’s fiscal stance shows improvement as a result of fiscal consolidation and fiscal reforms during the sample period. This is shown by the improved calculated IFS algorithm on average, which the value improved from 1.465 in 1970–1993 to 1.377 in 1998–2004 and to 1.146 in the 2006–2013. From the policy front, this indicator can serve as a precautionary early warning measure in formulating future fiscal path for Malaysia. This can be executed by targeting debt ratio and shifting the allocation of expenditures away from less efficient toward more growth-enhancing ones, which eventually would regain fiscal space to counter any incoming economic shocks in the future. This can enhance the fiscal transparency and assist in formulating a fiscal policy strategy in Malaysia.